Transmission coefficient and two-fold degenerate discrete spectrum of spin-1 bosons in a double-step potential - Oliveira, Luiz P. de; Castro, Antonio S. de [UNESP] (World Scientific Publ Co Pte Ltd, 2015)
The scattering of spin-1 bosons in a nonminimal vector double-step potential is described in terms of eigenstates of the helicity operator and it is shown that the transmission coefficient is insensitive to the choice of the polarization of the incident beam. Poles of the transmission amplitude reveal the existence of a two-fold degenerate spectrum. The results are interpreted in terms of solutions of two coupled effective Schrodinger equations for a finite square well with additional delta-functions situated at the borders.
Keywords: Vector bosons; DKP equation; double-step potential